Effectiveness of knowledge management in achieving success in Malaysian government agencies: A literature review - Sabaghpour Azarian, Mahdieh; Yunus, Yunura Azura; Ahmad Dahlan, Abdul Rahman (International Foundation for Research and Development, 2013)
As knowledge is being accepted as an inseparable imperative strategy of organization, organizations look at knowledge as a power, which drives advantages to them. However, many organizations believe it is not about just the existence of knowledge but the organizational growth is being driven from the act of knowledge sharing. As modern economy, takes knowledge as a point to achieve project success, this competitive advantage is being utilized from the greater degree of inter-organizational utilization of information and data coupled with the harnessing of people’s skills and ideas as well as their commitments and motivations. Therefore, it is undeniable that today's knowledge is an essential asset of every single company and it has become more important than land, labor or capital in today’s economy. This paper investigates on the importance of knowledge management in generating of project success by analyzing whether or not government companies and agencies in Malaysia practice Knowledge Management. In this regard, a research has been conducted amongst fifteen Malaysian governmental companies and agencies to find how effective project managers in Malaysian government companies, integrate Knowledge Management criteria and key success elements in order to achieve project success and gain success.